SAVI Approach Paper 12: Managing Programme Finances to Support Adaptiv e, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governa nce in ways that are effective in influencing reform, and that are abl e to take on a life of their own without continuing donor support. SAV I is also an adaptive programme, putting learning and adaptation at th e centre of all decision-making. Money is used and...